2020
DOI: 10.1017/s0033291720000161
|View full text |Cite
|
Sign up to set email alerts
|

Haematologic malignancies associated with clozapine v. all other antipsychotic agents: a pharmacovigilance study in VigiBase®

Abstract: Background Clozapine is mainly used in patients with treatment-resistant schizophrenia and may lead to potentially severe haematologic adverse events, such as agranulocytosis. Whether clozapine might be associated with haematologic malignancies is unknown. We aimed to assess the association between haematologic malignancies and clozapine using Vigibase®, the WHO pharmacovigilance database. Methods We performed a disproportionality analysis to compute reporting odds-ratio adjusted for age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 39 publications
(57 reference statements)
5
27
0
Order By: Relevance
“…This principally involved interrogating the VigiBase®, which is the global pharmacovigilance database maintained by the WHO, and previously used to evaluate ADEs associated with hydroxychloroquine [24,25]. VigiBase® contains all ICSRs of adverse events collected by the national pharmacovigilance centers from over 130 countries [26][27][28]. An ICSR is an anonymised report for a single individual (patient) who was given suspected drug, who experienced single or multiple ADEs.…”
Section: Methodsmentioning
confidence: 99%
“…This principally involved interrogating the VigiBase®, which is the global pharmacovigilance database maintained by the WHO, and previously used to evaluate ADEs associated with hydroxychloroquine [24,25]. VigiBase® contains all ICSRs of adverse events collected by the national pharmacovigilance centers from over 130 countries [26][27][28]. An ICSR is an anonymised report for a single individual (patient) who was given suspected drug, who experienced single or multiple ADEs.…”
Section: Methodsmentioning
confidence: 99%
“…Clozapine has been widely available for decades but remains underused due to safety issues, which include severe hematologic and cardiovascular adverse effects. Hematologic adverse effects include neutropenia, agranulocytosis (incidence of 3.0% and 1.0% over a follow-up of 4.5 years in the United Kingdom and Ireland, respectively), and more rarely anemia, thrombocytopenia but also potentially hematologic malignancies (Chrétien et al, 2020). Cardiovascular adverse effects include myocarditis (incidence of 3.16% over a follow-up of 6.5 years; Higgins, San, Lagnado, Chua, & Mihic, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Clozapine is bioactivated in a nitrenium ion by cytochromes P450 and myeloperoxidase system in leukocytes and their precursors. This nitrenium ion is a reactive species which has been associated with the formation of DNA adducts and cells apoptosis and is the probable cause of hematologic adverse effects (Chrétien et al, 2020). It has been shown in vitro that this clozapine nitrenium ion is normally detoxified by conjugating to glutathione (Dragovic, Boerma, van Bergen, Vermeulen, & Commandeur, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We have read with interest the reply by De Leon et al (Leon, las Cuevas, Sanz, & Verdoux, 2020 a ) about our work assessing the association between clozapine and haematological malignancies (Chrétien et al, 2020) in VigiBase ® . We are grateful that De Leon et al showed such interest in our study and we think that their remarks merit further explanations to be fully addressed.…”
mentioning
confidence: 97%